STUDENT WORKSHEET TO PRACTICE GEOSCIENCE LITERACY FOR 7th GRADE JUNIOR HIGH SCHOOL STUDENTS - RACHMADANI HAMID, SERLY; NURIL MAULIDA FAUZIAH, AN (PENSA E-JURNAL: PENDIDIKAN SAINS, 2019)
The aim of this study was to develop a feasible worksheet for 7th grade Junior High School students to practice geoscience literacy. The worksheet mainly focused on three aspects of scientific literacy: knowledge (content science); competencies (process science); and context science, and analogy observation which uses plate tectonic boundaries as its content. The Research design used in this study was Research & Development (R&D). The results showed that based on the modus of the worksheet was valid with score 4 for didactic, 4 for construction, and 3 for technical. The worksheet was also effective N-gain score was 0,81. Based on those results, it can be concluded that the developed student worksheet was very feasible to be used. Keywords: Student worksheet, geoscience literacy, analogy observation